Function, Role, Limitation, and Potential of Space Syntax Analysis in Architectural Field - Fitria Khairanisa (Universitas Atma Jaya Yogyakarta, 2022)
This study aims to determine the function, roles, limitations, and potential of spatial configuration analysis with Space Syntax. The development of digital technology affects the development of science, including in the field of architecture. Digital technology is not only a design visualization tool but also a part of the design process and a thinking tool for architects in designing. One of them is the Space Syntax program. Space Syntax is a quantitative analysis tool used to analyze the pattern of relationships between spaces in various forms of architectural space: buildings, cities, interiors, and landscapes. The method used in this research is the literature study method. Data collection techniques are collecting several sources from the internet and journal references that discuss using the Space Syntax program. The results of this study indicate that Space Syntax has a function, roles, limitations, and potential in analyzing architectural space. SpaceSyntax can explore various horizontal space scales, including buildings objects and urban areas. However, the findings show that Space Syntax has limitations. Some studies use a combination of other methods to overcome this limitation. The combination method also raises the potential of Space Syntax as an analysis tool in the architectural field.